Kepemimpinan Kepala Pesantren dalam Implementasi Program Wajar Dikdas di Pondok pesantren Salafiyah (Studi Kasus di PP. Daruttaâ'lim Waddaâ'wah Malang). - Ahmad Muammar; Zaedun Na'im (Leadership: Jurnal Mahasiswa Manajemen Pendidikan Islam, 2019)
Many students from the Salafiyah Islamic boarding school cannot continue their education to a higher level because of constraints in formal diplomas. Basic education program is one of the programs of the Ministry of Religion to overcome this. However, in its implementation it depends on the pesantren's own stakeholders, such as the role of the pesantren caregivers, pesantren head and pesantren instructors. Like in PP. Darutta'lim Wadda'wah Malang, which is one of the pesantren in Malang that has implemented a fair education program. In this case, the role of the head of the pesantren is very influential. Therefore, researchers are interested in carrying out research related to how the leadership of the pesantren head in implementing the fair education program. The focus of this research is about (1) How is the leadership of the pesantren head (2) how is the implementation of this program and also (3) what are the supporting factors and inhibiting factors of the program.The results of this study found that (1) Leadership characteristics of Darutta'lim Wadda'wah Islamic boarding school leadership in the implementation of the Elementary Education Program included in a democratic leadership style, including: Prioritizing deliberation in decision making, involving pesantren stakeholders in making policy, and providing opportunities to all pesantren stakeholders to give their opinions for the achievement of the success of the Elementary Education Program at the Darutta'lim Wadda'wah boarding school. (2) Implementation of the Basic Education Fair Program in PP. Darutta'lim Wadda'wah started with the socialization of the Ministry of Education, after the socialization activities, the City Ministry of Education also provided guidance to pesantren who wanted to implement the Elementary Education Program in their pesantren. Guidance includes how the licensing process to how the evaluation later. (3) Supporting factors for the implementation of the Basic Education Program at the Darutta'lim Wadda'wah boarding school include: the support of pesantren caregivers, the availability of educational infrastructure, experienced teaching staff, and the availability of supporting books. While the inhibiting factors include: the lack of time for learning activities, the tutor has not been able to get an educator certificate, the problem of funding, although getting assistance from BOS funds, the size depends on the number of students, learning facilities are still lacking, and limited teaching time for teachers.